The Evolution of International Collaborations in the Light of Disciplinary Interplay at Eötvös Loránd University in Budapest, Hungary – a Bibliometric Case Study - Kohus, Zsolt; Baracskai, Zoltán; Czakó, Katalin (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2020)
Scientometric and bibliometric analyses, focusing exclusively on the written output of research, are well-known methods to analyse the scientific performance of researchers and higher educational institutions. However, most studies lack the analysis of the interplay between different scientific disciplines or interdisciplinary research, often associated with higher research impact. The remaining studies intend to explore the connection between major scientific outputs and interdisciplinary nature of collaboration; however, the research interest is focused on a generalized national or international environment with a focal point on individual research fields. These studies do not take into account the contribution of individual universities, higher educational institutions and research facilities. To fill this gap, the paper combined a bibliometric analysis and measured the interplay between individual scientific disciplines of the written research output of Eötvös Loránd University in Budapest, Hungary. The novelty of this paper lies in the data correction of the parameters of the published papers marked as international collaboration on the Web of Sciences database; and the subsequent longitudinal evaluation and visualisation of interdisciplinary nature of research. The presented method establishes a new, potential framework being able to measure the scientific performance of higher educational institutions and its possible relevance during their evaluation. In the practical domain, the study can stimulate an incorporation of a new approach for higher educational institutions and decision-makers to analyse the interdisciplinary nature of research of written scientific outputs, which can serve as a potential indicator of research performance. Keywords: international collaboration, bibliometric data, interplay between disciplines, data correction of parameters, interdisciplinary nature of research